Investiture ceremony of the 24th president of DLSU - Office of the President - De La Salle University, Manila (Animo Repository, 2021)
De La Salle University hold the Investiture ceremony of its 24th President Br. Bernard S. Oca FSC on October 7, 2021 at the Most Blessed Sacrament Chapel. The ceremony began with a Eucharistic Celebration at 9:00 am.